PENGEMBANGAN E-MODULE IPA BERTEMA ANIME ONE PIECE PADA MATERI GETARAN, GELOMBANG, DAN CAHAYA - Aditya Putra Pratama; Aditya Rakhmawan; Nur Qomaria; Aida Fikriyah; Sunu Wahyudhi (Natural Science Education Research, 2026)
The development of an e-module with the theme of One Piece anime on the material of vibration, waves, and light aims to determine the validity of the media, the readability of the media, and the responses of students at SMPN 3 Kamal on the material of vibration, waves, and light. The development model in this study uses the ADDIE development model. The development instruments used are validation sheets from material experts, media experts, readability questionnaires, and response questionnaires. Data collection methods use questionnaires, interviews, and observations. By using descriptive data analysis techniques, namely validity tests using validation questionnaires filled out by validators to assess the validity of the developed products. The results of this study are that the One Piece anime-themed Science E-module on the material of vibration, waves, and light has been validated and meets the criteria for good learning media and is suitable for use in science learning, where 1.00 validation by material experts, 1.00 validation by media experts. The readability questionnaire trial obtained a total average of 97% in individual tests, and 94% in small group tests. Meanwhile, the student response questionnaire trial obtained an average total of 100% in the individual test and 94% in the small group trial.